PENINGKATAN KECERDASAN LOGIKA MATEMATIKA ANAK USIA 5-6 TAHUN MELALUI MEDIA MAZE ANGKA - Maya Wajannati (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2016)
This Research motivated by logic mathematical intelligence low of children aged 5-6 years in TK PGRI 1 Kota Serang, Banten, with observation of pre-study shows the percentage of 26%. This in indicated with the child still difficult to sort objects large and small, have not been able to raise the figure to the right order, have not been able to classify objects, not yet able to distinguish geometric forms, and write the numbers upside down. Therefore, this study aims to (1) investigate the implementation of the use of media maze number in logic mathematical intelligence to improve of children aged 5-6 and (2) to identify increasing logic mathematical intelligence of children aged 5-6 years in TK PGRI 1 Kota Serang, Banten once implemented activities using number maze. The method used is Action Research (PT). The subjects were children in group B consisted of 12 children: six girls and six boys. This research was conducted in TK PGRI 1 Kota Serang, Banten located on the street KH. Abd. Fatah Hasan Blok G-4 No. 26 Ciceri Permai Serang. The technique of collecting data through observation, field notes, interviews, and documentation. The research was carried with 2 cycles of the first cycle consists of 8 times the action and the second cycle consists of 3 times the action. Data analysis techniques used are qualitative and quantitative data. Based on this research, it is known that the application of learning activities of number maze has three stages: (1) preparation; RPPH researchers prepare and introduce the media; 2) implementation of activities and 3) evaluation. Logical-mathematical intelligence of child evolved significantly after the implementation of activities used number maze. The results of logic mathematical intelligence of children percentage in the first cycle is 52% and the percentage of logic mathematical intelligence of the child at the end of the second cycle of 82%. The results of data analysis showed that the implementation of activities used number maze to improve logic mathematical intelligence of children aged 5-6 years in TK PGRI 1 Kota Serang, Banten.